Conspicuous Consumption of Time: When Busyness and Lack of Leisure Time Become a Status Symbol - Bellezza, Silvia; Paharia, Neeru; Keinan, Anat (Journal of Consumer Research, 2017)
Abstract While research on conspicuous consumption has typically analyzed how people spend money on products that signal status, this article investigates conspicuous consumption in relation to time. The authors argue that a busy and overworked lifestyle, rather than a leisurely lifestyle, has become an aspirational status symbol. A series of studies shows that the positive inferences of status in response to busyness and lack of leisure time are driven by the perceptions that a busy person possesses desired human capital characteristics (e.g., competence and ambition) and is scarce and in demand in the job market. This research uncovers an alternative kind of conspicuous consumption that operates by shifting the focus from the preciousness and scarcity of goods to the preciousness and scarcity of individuals. Furthermore, the authors examine cultural values (perceived social mobility) and differences among cultures (North America vs. Europe) to demonstrate moderators and boundary conditions of the positive associations derived from signals of busyness.